Coherent thermal radiation of Fabry-Perot resonator structures - Kollyukh, O.G.; Kyslyi, V.P.; Liptuga, A.I.; Morozhenko, V.; Pipa, V.I.; Venger, E.F. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2007)
The coherent thermal radiation from semiconductor plane-parallel resonator structures is investigated both theoretically and experimentally. The coherent properties of thermal radiation from these objects are manifested by sharp spectral lines and wellpronounced lobe-like directional patterns. We investigated the dependences of the intensities of spectral lines and the angular distribution of thermal radiation on optical parameters of the structures. New optical effects are presented, namely, the modulation of the coherent thermal radiation spectrum by an external magnetic field and a uniaxial pressure.